Scheduling of irrigation in snap bean (Phaseolus vulgaris var. nanus) using canopy temperature - Helyes, L.; Pék, Z.; Varga, Gy.; Dimény, J. (International Journal of Horticultural Science, 2005)
The present paper evaluates the result of irrigation experiments carried out on snap beans sown in spring and summer and grown with and without irrigation. The experiments were run over the course of 12 years. In the average of 12 years, the yield was 2.8t ha-I for spring sown and 1.9 t ha-I in summer-sown plants without irrigation. The lowest level of profitable production, the 5.5t ha-I was reached twice in the case of spring sowing and only once in the case of summer sowing. Profitable yield production can be ensured only with regular irrigation and thus the yield may be increased by 4-5 times. In four of the twelve years we determined the canopy surface temperature of snap bean stands with and without irrigation. A Raynger II infrared remote thermometer determined the canopy surface temperature every day at 13.00 hours. The canopy temperature can well characterize the water supply of plant stands. This parameter may be used for describing the degree of drought and the water turnover of plant stands with different water supply. The positive values of foliage-air temperature differences (SDD) numerically express the degree of drought and the water supply of the crops. The results indicated that a 1 °C higher SDD value may cause 90-130 kg/ha yield loss.